Campus view with old Engineering Hall and Frosh Pond, University of Washington, n.d.
Engineering Hall built in 1908 as the Machinery Pavilion for the Alaska Yukon Pacific Exposition. Filed in: UW - Engineering Hall (Old) (#433).